2011
DOI: 10.1183/09031936.00031810
|View full text |Cite
|
Sign up to set email alerts
|

Impact of inspiratory muscle training in patients with COPD: what is the evidence?

Abstract: A meta-analysis including 32 randomised controlled trials on the effects of inspiratory muscle training (IMT) in chronic obstructive pulmonary disease (COPD) patients was performed. Overall and subgroup analyses with respect to training modality (strength or endurance training, added to general exercise training) and patient characteristics were performed. Significant improvements were found in maximal inspiratory muscle strength (PI,max; +13 cmH 2 O), endurance time (+261 s), 6-or 12-min walking distance (+32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
387
7
35

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 440 publications
(452 citation statements)
references
References 71 publications
(113 reference statements)
23
387
7
35
Order By: Relevance
“…Such reductions, when of 1 point or more, are considered clinically important differences. 8 Sustained maximum inspiratory pressure Such results are consistent with previous studies, which showed that inspiratory muscle training increases abdominal mobility 10 and significantly decreases dyspnea, 30,31,34 which is paramount in patients with COPD in pulmonary rehabilitation programs.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Such reductions, when of 1 point or more, are considered clinically important differences. 8 Sustained maximum inspiratory pressure Such results are consistent with previous studies, which showed that inspiratory muscle training increases abdominal mobility 10 and significantly decreases dyspnea, 30,31,34 which is paramount in patients with COPD in pulmonary rehabilitation programs.…”
Section: Discussionsupporting
confidence: 81%
“…However, a cutoff of Յ60 cm H 2 O was chosen because it is referenced for COPD. 8 It was observed that those subjects with respiratory muscle weakness had greater strength and endurance improve- It is important to emphasize that the strength gains were not clinically significant, unlike the increases in endurance. In addition, dyspnea decreased more in those subjects without muscle weakness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations